The strategic analysis and operation of the multiservice model used for synchronous transmission in communication networks - T. Kiruthiga; A. Vaniprabha (BOHR Journal of Computational Intelligence and Communication Network, 2023)
The core idea of asynchronous transfer mode (ATM) technology was revealed a long time ago. The main technology under development at the time was time-division multiplexing (TDM) technology, which consisted of synchronous switching based on the sequence number of bytes in the integrated frame. The main disadvantage of TDM technology, also known as synchronous transport module (STM) synchronous transmission technology, is the inability to reallocate the bandwidth of the integrated channel between subchannels. During those periods when no user data is sent on the subchannel, the aggregated channel still sends the bytes of this subchannel filled with zeros. Efforts to load sub channels’ idle periods necessitate the introduction of a header for each subchannel’s data. In intermediate statistical time-division multiplexing (STDM) technology, which allows idle periods to be filled by transmitting bursts of traffic from other sub channels, headers that actually have a subchannel number are introduced. In this paper, the strategic analysis and operation of technologies used in multiservice networks were discussed. Simultaneously, the structure of data sets is drawn into sets resembling computer networks. The fact that each packet has an address allows it to be transmitted asynchronously since its location relative to data on other subchannels is not its address. Asynchronous packets from one subchannel are inserted into the free time slots of another subchannel, but they are not mixed with the data of this subchannel because they have their own address.